2020
DOI: 10.3389/fpsyg.2020.00463
|View full text |Cite
|
Sign up to set email alerts
|

Creative Mindsets: Scale Validation in the Chinese Setting and Generalization to the Real Workplace

Abstract: Creative mindsets reflect the implicit beliefs individuals hold regarding the nature of creativity as innate (i.e., fixed mindset) or malleable (i.e., growth mindset). Karwowski (2014) developed the Creative Mindsets Scale (CMS), in which fixed and growth creative mindsets were each measured with five items. Across three studies, the current study aimed to examine its psychometric properties in Chinese settings and to explore to what extent effects of creative mindsets on creativity were generalized to the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 60 publications
(144 reference statements)
4
20
0
1
Order By: Relevance
“…Studies have suggested that various task and individual factors can influence divergent thinking performance ( Baas et al 2011 , 2015 ; Mehta et al 2012 ). Among them, the role of individuals’ creative mindsets in creative thinking is a research hotspot ( Hass et al 2016 ; Jia et al 2019 ; Karwowski 2014 ; O’Connor et al 2013 ; Zhou et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that various task and individual factors can influence divergent thinking performance ( Baas et al 2011 , 2015 ; Mehta et al 2012 ). Among them, the role of individuals’ creative mindsets in creative thinking is a research hotspot ( Hass et al 2016 ; Jia et al 2019 ; Karwowski 2014 ; O’Connor et al 2013 ; Zhou et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These two types of creative mindsets are relatively independent dimensions, rather than two opposite poles of the same continuum ( Karwowski 2014 ; Karwowski et al 2019 ). Studies have demonstrated the different consequences of creative mindsets on creative tasks ( Hass et al 2016 ; Karwowski 2014 ; O’Connor et al 2013 ; Zhou et al 2020 ; Royston and Reiter-Palmon 2017 ). For example, O’Connor et al ( 2013 ) examined the relationship between creative mindsets and a series of creative tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the small but negative correlation between fixed and growth creative mindsets is consistent with a recent set of studies conducted in China (Zhou et al ., 2020) illustrating that the two are somewhat independent constructs, and not part of a continuum (see also Katz‐Buonincontro et al, 2020). In addition, we found a moderate positive correlation between growth creative mindset and creative self‐efficacy reported elsewhere (Hass et al, 2018; Katz‐Buonincontro et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it is important to include both constructs in the measurement of teacher beliefs about creativity. For example, there is a robust correlation between endorsement of a growth creative mindset and self‐reported creative self‐efficacy (e.g., Karwowski, 2014; Katz‐Buonincontro et al, 2016; Zhou, Yang, & Bai, 2020). However, results of studies linking mindsets to creative behaviours have been mixed (Hass et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation